The feasibility and acceptability of mobile application-based assessment of suicidality using self-report components of a novel tool, the Suicide Ideation and Behavior Assessment Tool (SIBAT). (January 2022) - Chan, Eric C; Wallace, Keanna; Yang, Esther H; Roper, Leslie; Aryal, Garima; Lodhi, Rohit J; Isenberg, Richard; Carnes, Patrick; Baskys, Andrius; Green, Bradley; Aitchison, Katherine J
Highlights: The Suicide Ideation and Behavior Assessment Tool (SIBAT) was administered. Participants responded using their mobile device or personal computer. There was good concurrent validity between the two methods of data collection. Greater rates of scale completion were observed in the mobile device group. Abstract: The aim of this study was to assess the validity of a mobile application-based self-report questionnaire in the assessment of suicidality. We developed a program for the administration of self-report components of the Suicide Ideation and Behavior Assessment Tool (SIBAT). We invited university students and trainees enrolled in a study of addictions to complete this component of the SIBAT using the program on their mobile devices or personal computer. 196 participants completed all required modules of the SIBAT, with 97 using their mobile device and 99 using their personal computer. Rates of completed questionnaires between the two groups were compared, as were the responses to the items and the total scores. There was a significant difference between proportions of scale completion in both groups, with a greater number of participants who used a personal computer to complete the scale not responding to all questions compared to participants who used a mobile device to complete the scale. Data collected via mobile device showed good concurrent validity with data collected via personal computer. A trend toward greater disclosure of suicidality was observed in the mobile device group however, replication of these findings using larger sample sizes is needed.